Public regulatory arrangements for private higher education in the Western Balkans. (November 2017) - Papadimitriou, Antigoni; Levy, Daniel C; Stensaker, Bjørn; Kanazir, Sanja
The article presents an analysis of the developments of higher education laws and regulations in the Western Balkans for the period 1990–2015, with the aim of mapping the regulatory arrangements for the private higher education sector and to explore the relationship between public and private higher education in the region. Based on a conceptual framework highlighting the competitive and complementary regulatory design options available in current governance arrangements, the study finds much ambiguity in policy designs regarding how private and public higher education should co-exist in the Western Balkans. As such, it is argued that the study contributes to a better understanding of the unclear role private higher education is playing in the development of the region.